2012
DOI: 10.1007/s12350-012-9548-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of left ventricular function and the extent of ischemia and scar by stress myocardial perfusion imaging on prognosis and therapeutic risk reduction in diabetic patients with coronary artery disease: Results from the Bypass Angioplasty Revascularization Investigation 2 Diabetes (BARI 2D) trial

Abstract: Background The Bypass Angioplasty Revascularization Investigation 2 Diabetes trial demonstrated similar long-term clinical effectiveness of revascularization (REV) and intensive medical (MED) therapy. Comparisons of post-intervention ischemic burden have not been explored but are relevant to treatment decisions. This study examined differences in 1-year stress myocardial perfusion SPECT (MPS) abnormalities by randomized treatment. Methods MPS was performed in 1,505 patients at 1-year following randomization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 133 publications
(73 citation statements)
references
References 16 publications
3
59
0
11
Order By: Relevance
“…There is robust evidence that myocardial burden size of functional myocardial ischemia and ischemia-related left ventricular dysfunction both of which are assessed simultaneously by stress electrocardiogram-gated myocardial single-photon emission computed tomography have mid-to long-term cardiac events. [15][16][17][18] Together with the issue previously mentioned, two types of non-negligible false positive features in the assessment of anatomical narrowing by coronary CT angiography and functional ischemia by stress myocardial CT perfusion imaging have to be furthermore overcome for the improvement in the clinical values of the presented findings so that their complementary assessment using a contrast medium and a stress agent could be more effective in the clinical setting.…”
Section: See Related Article Pp 1253-1262mentioning
confidence: 99%
“…There is robust evidence that myocardial burden size of functional myocardial ischemia and ischemia-related left ventricular dysfunction both of which are assessed simultaneously by stress electrocardiogram-gated myocardial single-photon emission computed tomography have mid-to long-term cardiac events. [15][16][17][18] Together with the issue previously mentioned, two types of non-negligible false positive features in the assessment of anatomical narrowing by coronary CT angiography and functional ischemia by stress myocardial CT perfusion imaging have to be furthermore overcome for the improvement in the clinical values of the presented findings so that their complementary assessment using a contrast medium and a stress agent could be more effective in the clinical setting.…”
Section: See Related Article Pp 1253-1262mentioning
confidence: 99%
“…They found that the reduction of ischemia by revascularization and extent of scar as defined on SPECT at 1 year to be powerful predictors of patient outcome. 164 …”
Section: More Recent Clinical Studies Bari 2d: Myocardial Perfusion Smentioning
confidence: 99%
“…[18][19][20] The DIAD study reported that 22% of asymptomatic diabetic patients had myocardial ischemia on adenosine Tc-99 m SPECT MPI, 18 and subsequent COURAGE, INSPIRE, and BARI-2D trials confirmed the powerful incremental risk assessment with SPECT MPI as well as favorable effects of optimal medical therapy in patients with CAD and/or DM. [21][22][23] In the current issue of the Journal of Nuclear Cardiology, Morales et al report a large retrospective analysis of 17,499 patients undergoing SPECT MPI at a single tertiary center from 1996 to 2006. 24 The study explores the interaction of risks of subsequent hard coronary events identified by diabetes mellitus, history of CAD, and the presence of greater than mild stress perfusion defect (SSS C 4) 24 equivalent to a 6% total stress LV perfusion defect score.…”
mentioning
confidence: 99%